'Let's Talk about Emotions!'. The Effect of Conversational Training on Preschoolers' Emotion Comprehension and Prosocial Orientation. Issue 1 (18th August 2014) - Ornaghi, Veronica; Grazzani, Ilaria; Cherubin, Elisa; Conte, Elisabetta; Piralli, Francesca
Abstract We investigated whether conversational intervention focused on emotions could promote the development of emotion comprehension (EC), theory of mind (ToM), and prosocial orientation in preschoolers. Seventy‐five 4‐ to 5‐year‐old children (Mage at pre‐test: 5 years and 1 month; standard deviation = 6.83 months), assigned to experimental and control conditions, were pre‐ and post‐tested for verbal ability, EC, false‐belief understanding, and prosocial orientation. Over a 6‐week intervention, all children were presented with brief illustrated scenarios based on emotional scripts. The training group was then involved in conversations about the nature, causes, and regulation of emotion whereas the control group engaged in free play, where conversation was minimized. The training group outperformed the control group in EC and prosocial orientation, even after controlling for gains in verbal ability whereas no differences were found for children's false‐belief understanding. The positive effect remained stable over time. Practical implications of the findings are discussed.